Essential Oil Extraction from Citronella (Cymbopogon nardus L.) Using Solvent-Free Microwave Extraction Method (SFME) - Siti Fatimah; Ditta Kharisma Yolanda Putri (University of Jember, 2022)
Indonesia is one of the countries that produces essential oils, a commodity that can generate foreign exchange. Therefore, essential oils receive special attention from the Indonesian government. Indonesia generates 40-50 types of plants that produce essential oils and are traded worldwide. Extraction using a microwave, with the basic mechanism of microwave heating, involves stirring polar molecules or ions that oscillate due to the influence of electric and magnetic fields, called dipolar polarization. From the results of physical analysis, citronella essential oil obtained using the Solvent FreeMicrowave Extraction (SFME) method has met the standards and quality of citronella oil based on SNI 06-3953-1995, according to the parameters of color, specific gravity, and solubility in water. 80% ethanol shows citronella oil of good quality. The results of GC-MS (Gas Chromatography-Mass Spectrometry) analysis on the extraction of citronella essential oil using the Solvent Free Microwave Extraction (SFME) method obtained two components, namely citronella and geraniol, with citronellal percentages of 8.64% and 7.53%. Optimal operating conditions for extracting essential oils from citronella raw materials using the Solvent Free Microwave Extraction (SFME) method.